2018
DOI: 10.3389/fphys.2018.00748
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Protein Profile in Honeybees: Caste and Task Matter More Than Age

Abstract: Reproductive and task partitioning in large colonies of social insects suggest that colony members belonging to different castes or performing different tasks during their life (polyethism) may produce specific semiochemicals and be differently sensitive to the variety of pheromones involved in intraspecific chemical communication. The main peripheral olfactory organs are the antennal chemosensilla, where the early olfactory processes take place. At this stage, members of two different families of soluble chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Worker gene expression was most strongly associated with behavioural specialization, as, for example, illustrated by the finding of ten times more differentially expressed genes (DEGs) between brood carers and foragers than between young and old, or fertile and infertile workers. Gene expression being more strongly associated with behavioural specialization than with age is consistent with previous age‐controlled transcriptomic (Alaux et al, ; Whitfield et al, ) and proteomic (Iovinella et al, ) studies on honeybee workers but has so far not been shown in other social insects. In contrast, an age‐controlled comparison of queens and workers revealed more DEGs associated with age than with caste in the ant Lasius niger (Lucas et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Worker gene expression was most strongly associated with behavioural specialization, as, for example, illustrated by the finding of ten times more differentially expressed genes (DEGs) between brood carers and foragers than between young and old, or fertile and infertile workers. Gene expression being more strongly associated with behavioural specialization than with age is consistent with previous age‐controlled transcriptomic (Alaux et al, ; Whitfield et al, ) and proteomic (Iovinella et al, ) studies on honeybee workers but has so far not been shown in other social insects. In contrast, an age‐controlled comparison of queens and workers revealed more DEGs associated with age than with caste in the ant Lasius niger (Lucas et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The potential biological significance of genes could be derived from their transcript expression profiles [24]. It is widely believed that the OBPs specifically expressed in antennae play a role in the olfaction of insects [25,26], while the ones expressed elsewhere may get involved in the non-chemosensory processes [27][28][29]. According to the qRT-PCR results, the AcerOBP6 transcript was primarily expressed in the antennae of forager bees and significantly more expressed than in the antennae of drones, suggesting that AcerOBP6 may play an essential role in recognizing general odorants compared to sex pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-synthase has caste specific expression in the weaver ant 46 (OG0006255 and OG0006612) and esterase E4-like (OG0000783) is upregulated in young honeybee queens compared to nurses at the proteomic level 47 . There are also other genes of interest, which to our knowledge have not previously associated with caste, including Toll-like receptor 8 (OG0001441) (see Supplementary Table S4).…”
Section: A Toolkit Of Many Genes With Small Effects Predicts Caste Across Different Forms Of Sociality In Waspsmentioning
confidence: 99%